2016
DOI: 10.3329/jujbs.v4i2.27790
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Regeneration of Grass Pea (Lathyrus sativus L.)

Abstract: In vitro regeneration protocol for grass pea (Lathyrus sativus L.) was optimized using different concentrations and combinations of growth regulators. Direct shoot regeneration obtained through shoot organogenesis from different explants of grass pea cultured on MS medium supplemented with Gamborg B5 vitamin containing 6-benzylaminopurine (BAP), Thidiazuron (TDZ) and ?-naphthalene acetic acid (NAA). Highest percentage of shoots were obtained at 4.0 mg/l of BAP on nodal explants. Stunted multiple shoots were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…Sucrose was shown to play a vital role in improving plant growth and shoot regeneration rate, while glucose and maltose played a minor role in shoot induction. The findings in the current study are consistent with previous studies which reported that sucrose induced shoot formation of Soybean [66], Velvet bean [67], Peach [68], Gotu Kola [16], Pea [69,70], Kris [71], Cucumber [72]. The types of carbohydrate sources, and their concentrations may influence culturing success [63,65].…”
Section: Discussionsupporting
confidence: 92%
“…Sucrose was shown to play a vital role in improving plant growth and shoot regeneration rate, while glucose and maltose played a minor role in shoot induction. The findings in the current study are consistent with previous studies which reported that sucrose induced shoot formation of Soybean [66], Velvet bean [67], Peach [68], Gotu Kola [16], Pea [69,70], Kris [71], Cucumber [72]. The types of carbohydrate sources, and their concentrations may influence culturing success [63,65].…”
Section: Discussionsupporting
confidence: 92%
“…A lo anterior, se puede sumar que el TDZ estimula la síntesis de auxinas endógenas (Murthy et al 1995, De Melo et al 2006) y se ha reportado que un aumento de las concentraciones de 3-ácido indolacético (IAA) en los sitios celulares induce anormalidades en el crecimiento, como inhibición de los brotes (disminución de la elongación y el área foliar) (Saha et al 2015).…”
Section: Resultados Y Discusiónunclassified
“…NLK-40 exhibited 92% response to callusing and it took 30-32 days to produce full grown green compact callus. Afterwards, Saha et al, (2015) highest percentage of shoots were obtained at 4.0 mg/l of BAP on nodal explants. Stunted multiple shoots were developed from nodal explants while 1.5 mg/l TDZ was used.…”
Section: Organogenesismentioning
confidence: 97%
“…The best rooting was achieved on MS medium containing 0.90 mg/l NAA. Saha et al, 2015). Tripathy et al, (2013) internode explants of grass pea (Lathyrus sativus L.) pre-cultured in B5 with 2,4-D (2 mg/l) + BAP (0.5 mg/l) when transferred to BM medium containing 0.5 mg/l NAA+2 mg/l BAP; produced conspicuous, glossy, dark green and well developed somatic embryos.…”
Section: Somatic Embriyogenesismentioning
confidence: 99%